Dendrite development regulated by the schizophrenia-associated gene FEZ1 involves the ubiquitin proteasome system - Watanabe, Yasuhito; Khodosevich, Konstantin; Monyer, Hannah (Cell reports, 2014)
Downregulation of the schizophrenia-associated gene DISC1 and its interacting protein FEZ1 positively regulates dendrite growth in young neurons. However, little is known about the mechanism that controls these molecules during neuronal development. Here, we identify several components of the ubiquitin proteasome system and the cell-cycle machinery that act upstream of FEZ1. We demonstrate that the ubiquitin ligase cell division cycle 20/anaphase-promoting complex (Cdc20/APC) controls dendrite growth by regulating the degradation of FEZ1. Furthermore, dendrite growth is modulated by BubR1, whose known function so far has been restricted to control Cdc20/APC activity during the cell cycle. The modulatory function of BubR1 is dependent on its acetylation status. We show that BubR1 is deacetylated by Hdac11, thereby disinhibiting the Cdc20/APC complex. Because dendrite growth is affected both in hippocampal dentate granule cells and olfactory bulb neurons upon modifying expression of these genes, we conclude that the proposed mechanism governs neuronal development in a general fashion.
Gesehen am 26.08.2020